Antibacterial Performance of Terpenoids from the Australian Plant Eremophila lucida - Israt J. Biva; Chi P. Ndi; Susan J. Semple; Hans J. Griesser (MDPI AG, 2019)
Plants in the Australian genus Eremophila (Scrophulariaceae) have attracted considerable recent attention for their antimicrobial compounds, which possess a wide range of chemical structures. As they are typically associated with the oily-waxy resin layer covering leaves and green branchlets, and Eremophila lucida is prominent among the species containing a pronounced sticky resin layer, this species was considered of interest for assessing its antibacterial constituents. The n-hexane fraction of the crude acetone extract of the leaves exhibited antibacterial activity against Staphylococcus aureus. Isolation led to the known compounds cembratriene, (3Z, 7E, 11Z)-15-hydroxycembra-3,7,11-trien-19-oic acid (1), the sesquiterpenoid, farnesal (2) and the viscidane diterpenoid, 5α-hydroxyviscida-3,14-dien-20-oic acid (3). The purified compounds were tested for antibacterial activity with 2 and 3 showing moderate antibacterial activity against Gram-positive bacteria.